Design of a patient monitoring system using 3D accelerometer sensors - Kallem, Devi Shravanthi (Kansas State University, 2010)
The Patient Monitoring System is a wireless sensor network application used for dynamically tracking a patient’s physical activity using 3D Accelerometer Sensors in the Sun Small Programmable Object Technology (SPOT) platform. The system is able to detect different postures of a person and recognize high-level actions performed by a patient by monitoring different pattern of postures. This activity can be monitored remotely from a nurse station or a handheld device. The monitoring system can be used for alerting the nurse station in a hospital, if a patient performs some abnormal action. In the proposed system, the Sun SPOTs are affixed on a person's chest, thigh, leg and arm. The application determines the posture of a person by sensing the acceleration and tilt values of the SPOT in the direction of X, Y and Z axis. Based on these values the application can determine the postures of a person such as Lying Down, Sitting, Standing, Walking, Bending, and Arm Moving. We provide user mechanisms to define high level actions such as “attempting to get up from Lying Down position”, in terms of patterns of lower-level posture sequences. The system detects these patterns from the posture sequences reported by the Sun SPOTs, and reports them at desired locations.
Keywords: Sun SPOT; Patient Monitoring System; 3D Accelerometer Sensor; Computer Science (0984)